Comparison of Different Combined Multiple Tunnel Complexes in Soft Soil under Seismic Vibrations - Ahsan Naseem; Wajahat S. Ansari; Muhammad Kashif; Asad Naseem; Shamsher Sadiq; Ken Schotte; Hans De Backer (Civil Engineering Journal, 2023)
The resilience of underground tunnels has gained paramount importance recently, driven by the need to ensure the safety and functionality of critical transportation and infrastructure systems during seismic events. Underground tunnels are prone to severe damage when the soil condition is poor and located in a high seismic zone. While the behavior of individual tunnels has been extensively studied, the concept of multiple tunnels combined into a large tunnel complex is relatively new, with limited available research focusing on rectangular-shaped tunnel complexes and requiring a more detailed examination. This study parametrically analyzes two novel and unconventional structures in soft soil, i.e., twin and triple tunnel complexes resulting from the combination of closely spaced circular twin and triple individual tunnels. Seismic records from Coyote (US, 1979), Kobe (Japan, 1995), and Kocaeli (Turkey, 1999) have been used to determine the produced surface displacements, tunnel distortions, lateral stresses on the tunnel structures, and the induced seismic forces, including thrusts, shear forces, and bending moments. The results are then compared with the conventional rectangular-shaped tunnel complex, which is also analyzed under the same conditions. The comparison shows that the twin and triple tunnel complexes are comparatively better seismic performers than the conventional rectangular tunnel complex, with reduced ground displacements produced, lesser incurred structural distortions, experienced lateral stresses, and induced seismic forces. Doi: 10.28991/CEJ-2023-09-12-01 Full Text: PDF